Community-Based Blood Donation Program: Sustainability and Local Capacity Building in these Changing Times of Demand in the Global Health - Sarong, Kim (Silliman Journal, 2023)
Blood’s growing use in various therapies has led to new regulations governing its collection, use, and storage. Ensuring a sustainable blood supply remains a challenge especially in the Philippines. Conducted in Brgy. Poblacion, Ayungon, Negros Oriental, this study assessed how young residents’ knowledge, attitudes, and practices relate to blood donation. Data was analyzed with SPSS and Excel 2010. The Chi-square Test of Independence assessed the KAP association, with p < 0.05 denoting statistical significance. Out of 76 respondents, 63.16% had average knowledge, 72.37% held positive attitudes, and 86.84% were willing to donate. Actual donation rates were low (14.47%) due to lack of awareness (50%), fear of needles (28.95%), and preference to donate to family and friends (22.37%). Encouraging awareness, incentivizing donations, and rural blood donation camps can address the limited blood supply issue.